Brazilian journal of plastic surgery: Analysis of articles published between 2010-2019 - Secanho, Murilo Sgarbi [UNESP] (2021)
Introduction: The Brazilian Journal of Plastic Surgery (RBCP-Revista Brasileira de Cirurgia Plástica)is the Brazilian Society of Plastic Surgery (SBCP-Sociedade Brasileira de Cirurgia Plástica) official publication and will complete 35 years of existence in 2021. During this period, few articles analyzed the content published by the journal. This work aims to carry out an analysis of articles published in RBCP between 2010 and 2019. Methods: Descriptive retrospective analysis of articles published in RBCP between 2010 and 2019. Inclusion criteria were articles present in the analyzed issues, of the type “Original Article,” “Review Article,” and “Case Report,” and not be a supplement edition. Results: A total of 1,107 articles were evaluated, of which 931 were included in the study; 700 “Original Articles” (75.2%), 66 “Review Articles” (7%) and 165 (17.8%) “Case Reports.” 3. 012 (73%) males and 1,108 (27%) females among the authors. Nine hundred fourteen articles were produced in Brazil. Of these, 577 (63.1%) in services accredited by Department of Education and Accredited Services (DESC-Departamento de Ensino e Serviços Credenciados) and 337 (36.9%) in non-accredited services. The main themes were aesthetics with 379 (40.7%) articles, followed by head and neck reconstruction with 115 (12.3%) and basic and experimental science with 114 (12.2%) publications. Conclusion: The data presented in this article allow a descriptive analysis of the RBCP. There is a need to intensify the publication of original articles and to discuss the search for gender equality in publications. Institutions that train residents to play an important role in national scientific production and scientific participation during training must be encouraged.